1978
DOI: 10.1136/jcp.31.7.666
|View full text |Cite
|
Sign up to set email alerts
|

gamma-Glutamyl transferase isoenzymes in human bile.

Abstract: suMMARY The y-glutamyl transferase isoenzymes of bile were studied using electrophoretic, gel filtration, and ultracentrifugation techniques. In view of the known association of other biliary enzymes with lipids the effects of butanol extraction were investigated. The results show the presence of four isoenzymes of y-glutamyl transferase in bile, differing in electrophoretic mobilities, molecular size, and density. The correlation between the properties of biliary y-glutamyl transferase and of alkaline phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This author, studying yGT in liver extract, bile, and a normal serum pool, showed that papain digestion and incubation with detergent each produced a smaller molecule, corresponding to isoenzymes SV and S111, respectively, in this study. The detergent effect upon biliary yGT confirmed our previous demonstration (Wenham et al, 1978a) that extraction of biliary yGT with n-butanol resulted in the production of a smaller molecule possessing identical physicochemical characteristics to isoenzyme Sill (Table 2), a process similar to that already proposed for biliary alkaline phosphatase (Price et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This author, studying yGT in liver extract, bile, and a normal serum pool, showed that papain digestion and incubation with detergent each produced a smaller molecule, corresponding to isoenzymes SV and S111, respectively, in this study. The detergent effect upon biliary yGT confirmed our previous demonstration (Wenham et al, 1978a) that extraction of biliary yGT with n-butanol resulted in the production of a smaller molecule possessing identical physicochemical characteristics to isoenzyme Sill (Table 2), a process similar to that already proposed for biliary alkaline phosphatase (Price et al, 1972).…”
Section: Discussionsupporting
confidence: 87%
“…In the case of yGT, it has been suggested that the biliary enzyme may be associated with lipid (Wenham et al, 1978a); furthermore, Beck (1978) suggested that a serum isoenzyme might be associated with a lipid component.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature, source and functional impor tance of the soluble form of GGT in blood plasma and CSF is still uncertain, but the esti mation of this activity in serum and bile is a valuable index of hepatobiliary function and its alteration [12,26,35]. Serum GGT activ ity is also increased in patients with brain tu mors and some other neurological diseases [10,26].…”
Section: Discussionmentioning
confidence: 99%